Childhood acute promyelocytic leukemia in a pediatric cancer referral center in Baghdad, Iraq. Improved results with ATRA extended consolidation. Issue 12 (15th October 2022) - Testi, Anna Maria; Al-Jadiry, Mazin Faisal; Ghali, Hasanein Habeeb; Fadhil, Samaher Abdulrazzaq; Al-Darraji, Amir Fadhil; Al-Saeed, Raghad Majid; Sabhan, Ahmed Hatem; Al-Badri, Safaa A. Faraj; Abed, Wisan Majeed; Ameen, Najiha Ahmed; Al-Tameemi, Ruaa Zaki; Al-Assaf, Arabiya Idan; et al.
Abstract: Modern treatments have dramatically improved the prognosis of childhood acute promyelocytic leukemia (APL). This progress has not yielded equivalent benefit in developing countries, where biological studies and supportive cares are insufficient and often unavailable. Since 2003, an all-trans retinoic (ATRA)-based, risk-adapted protocol was initiated in Baghdad. Patients were defined: high-risk with WBC ≥10 × 10 9 /L and standard-risk with WBC <10 × 10 9 /L. ATRA was included in induction and maintenance and, from 2010, in consolidation. Of 429 pediatric acute myeloid leukemia (September 2003–August 2019), 118 (27.5%) were APL. Six children died before therapy, 4 refused; 94/108 (87%) achieved a remission; 12 (11%) died early and 2 abandoned. The 5-year overall survival and event-free survival are 61.8% and 55.5% for all patients, 51.7% and 43.6% for first protocol, 68.4% and 63.9% for second one. Baseline WBC count was a risk factor for induction mortality; early hemorrhagic death remains a major cause of failure. ATRA extended consolidation improved results.